THE OBAMA ADMINISTRATION’S RUSSIA “RESET” POLICY AND THE SOUTHERN CAUCASUS - KHALIFAZADEH, Mahir (CENTRAL ASIA AND THE CAUCASUS, 2014)
This article reviews the key priorities of President Obama’s “reset” policy with Russia. The author analyzes the impact of the “reset” on the Southern Caucasus. He emphasizes the region’s strategic importance for U.S. policy toward both the Greater Middle East and the post-Soviet space. The author discusses the failure of the “Russia reset” to improve America’s interests, particularly in the Southern Caucasus. He also evaluates the Putin doctrine priorities and the implications of the Crimean crisis. The author calls for new U.S. initiatives to enforce peace, international borders, and America’s strategic interests in the Southern Caucasus and Central Asia.